Allogeneic stem cell transplantation in adult patients with acute myeloid leukaemia and 17p abnormalities in first complete remission: a study from the Acute Leukemia Working Party (ALWP) of the European Society for Blood and Marrow Transplantation (EBMT). Issue 1 (December 2017) - Poiré, Xavier; Labopin, Myriam; Maertens, Johan; Yakoub-Agha, Ibrahim; Blaise, Didier; Ifrah, Norbert; Socié, Gérard; Gedde-Dhal, Tobias; Schaap, Nicolaas; Cornelissen, Jan; Vigouroux, Stéphane; Sanz, Jaime; et al.
Abstract Background Acute myeloid leukaemia (AML) with 17p abnormalities (abn(17p)) carries a very poor prognosis due to high refractoriness to conventional chemotherapy, and allogeneic stem cell transplantation (allo-SCT) appears as the only potential curative option. Methods To address outcomes after allo-SCT in patients with abn(17p), we retrospectively analysed de novo or secondary AML undergoing SCT between 2000 and 2013 from the EBMT registry. Results One hundred thirty-nine patients with confirmed abn(17p) have been selected. At the time of transplant, one hundred twenty-five were in first remission (CR1). Median age was 54 years old. Abn(17p) was associated with a monosomal karyotype in 83% of patients, complex karyotype in 91%, monosomy 5 or 5q deletion (-5/5q-) in 55%, monosomy 7 (-7) in 39% and both -5/5q and -7 in 27%. Seventy-three patients (59%) had a reduced-intensity conditioning regimen. The 2-year overall survival (OS) and leukaemia-free survival (LFS) were 28 and 24%, respectively. The 2-year non-relapse mortality (NRM) was 15%, and 2-year relapse incidence (RI) was 61%. The cumulative incidence of grade II to IV acute graft-versus-host disease (GvHD) was 24% and that of chronic GvHD was 21%. In multivariate analysis, the presence of a -5/5q- in addition to abn(17p) was significantly and independently associated with worse OS, LFS and higher RI. Age and donor types did not correlate with outcome. Conditioning intensity was not statistically associated with OS, LFS and NRM when adjusted for patients' age. Conclusions In contrast to the dismal prognosis reported for AML patients harbouring abn(17p) undergoing conventional chemotherapy, allogeneic SCT provides responses in about 25% of those patients transplanted in CR1.